2021
DOI: 10.9734/ajeba/2021/v21i730399
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Earnings Response Coefficient in the Nigerian Post-IFRS Implementation Era

Abstract: Aims: The study assessed the determinants of earnings response coefficient in the Nigerian Post-IFRS implementation era. It critically looked at the impact of investors' protection, earnings persistency, and systematic risks on earnings response coefficients. Study design: The study adopted an ex-post facto research design. Methodology: A sample of 35 companies was drawn from the population of the listed companies in the Nigerian Stock Exchange between 2013 to 2020. Secondary data was used. The Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Susanto (2012) proves that systematic risk has a positive effect on ERC. Beredugo (2021) states that systematic risk has a negative effect on ERC, while Beredugo (2021) shows that systematic risk has no effect on ERC.…”
Section: Shiri Et Al (2012) Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Susanto (2012) proves that systematic risk has a positive effect on ERC. Beredugo (2021) states that systematic risk has a negative effect on ERC, while Beredugo (2021) shows that systematic risk has no effect on ERC.…”
Section: Shiri Et Al (2012) Andmentioning
confidence: 99%
“…According to Beredugo (2021), manufacturing companies are defensive with uncertainty always appearing. Even though the company's operations are going well and the stock price has no reason to down, according to efficient market theory, the market will still react negatively because of systematic risk (Basuki et al, 2017) Dividend payout ratio fails to moderate the positive effect of firm growth on ERC.…”
Section: Different Tests (Mannmentioning
confidence: 99%
“…The IFRS implementation has not resonated in the expected increase in investors' patronage as speculated. Indeed, the persistent apathy and waning investors' confidence that has beset the country's securities exchange in the previous few years kept on reflecting on market indices and continues to spark a steady fall in share prices of listed firms (Beredugo, 2021). Scott (2009) suggested that a number of reasons could be responsible for differential market response to reported earnings, which could be attributable to the information need on earnings persistence among others.…”
Section: Introductionmentioning
confidence: 99%
“…However, the resultant effect of IFRS on the decision usefulness of financial statements information, still remain a mirage among investors in Nigeria. Beredugo (2021) also added that IFRS implementation has not resonated in the expected increase in investors' patronage as speculated. Indeed, the persistent apathy and waning investors' confidence that has beset the country's securities exchange in the previous few years kept on reflecting on market indices and continues to spark a steady fall in share prices of listed firms (Beredugo, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Beredugo (2021) also added that IFRS implementation has not resonated in the expected increase in investors' patronage as speculated. Indeed, the persistent apathy and waning investors' confidence that has beset the country's securities exchange in the previous few years kept on reflecting on market indices and continues to spark a steady fall in share prices of listed firms (Beredugo, 2021). Affirmatively, investor responses to return sensitivity of published financial statement are very low.…”
Section: Introductionmentioning
confidence: 99%